Participation in and Compliance with Public Voluntary Environmental Programs: An Evolutionary Approach - Constadina Passa; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2004)
The joint evolution of participating and complying firms in a public VA, along with the evolution of the pollution stock is examined. Replicator dynamics modeling participation and compliance are combined with pollution stock dynamics. Fast-slow selection dynamics are used to capture the fact that decisions to participate in and further comply with the public VA evolve in different time scales. Evolutionary stable (ES) equilibria depend on the structure of the legislation and auditing probability. Partial participation and partial compliance can be ES equilibria, with possible multiplicities, in addition to the monomorphic equilibria of full (non) compliance. Convergence to these equilibria could be monotonic or oscillating. Full participation and compliance can be attained if the regulator is pre-committed to certain legislation and inspection probabilities, or by appropriate choices of the legislatively set emission level and the non-compliance fine.
Keywords: Q2; L5; 330; Voluntary agreements; Participation; Compliance; Evolutionary stability; Replicator dynamics; Selbstverpflichtung; Umweltschutz; Evolutionsökonomik